Mohandas Gandhi : experiments in civil disobedience - Ahmed, Talat (London : Pluto Press, 2019)
A new critical biography highlighting the contradictions in Gandhi's non-violent philosophy.
Cover; Contents; Illustrations; Acknowledgements; Glossary; Introduction; 1. Early Life: 1869-93; 2. South Africa and the Birth of Satyagraha: 1893-1915; 3. The Champion of the Oppressed Returns: 1915-19; 4. Nationalist Leader: 1919-29; 5. Global Icon: 1929-39; 6. Fascism, War, Independence and Partition: 1939-48; Conclusion: Assassination and Legacy; Notes; Index
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed January 22, 2019).
JSTOR
Keywords: Gandhi, -- Mahatma, -- 1869-1948.; Gandhi, -- Mahatma, -- 1869-1948; Civil disobedience; Passive resistance; Désobéissance civile; Résistance passive; HISTORY -- Asia -- India & South Asia; Civil disobedience; Passive resistance; Gandhi, Mahatma, 1869-1948; Nonviolence; Biography & Autobiography; Political Science; Electronic book